DETERMINATION OF CHROMATOGRAPHIC ASSAY AND VALIDATION OF OFLOXACIN IN BULK AND PHARMACEUTICAL DOSAGE FORM - M, Sumithra (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the study is simple, sensitive; eco-friendly reverse phase chromatographic method has been developed and validated for the quantitative determination of ofloxacin in bulk and marketed formulation. Method: The developed method was done using Hypersil silica C18 (250 mm × 4.6 mm, 5 μ particle size) as column and the mobile phase is containing water and methanol in the ratio of (10:90) vol/vol. The mobile phase pass at 1 ml/min flow rate and the eluted solution is measured at 270 nm using a PDA detector. Results: The assay method is linear from the concentration range of 5–30 μg/ml. The corelation coefficient is 0.9998. The mean percentage recovery for the developed method is found to be in the range of 98.4–100.6%. The developed method complies robustness studies. Conclusion: The validation of the developed method was done by as per the ICH guidelines. It obeys the linearity, accuracy, precision, and robustness studies. Validation parameters are within the limitations. The results of the developed process indicated the reverse phase chromatographic method is simple, accurate as well as precise, rapid and eco-friendly method for routine analysis of ofloxacin in bulk and its pharmaceutical dosage form.